Ventricular activation during sympathetic imbalance and its computational reconstruction. - Nash, M; Thornton, J; Sears, C; Varghese, A; O'Neill, M; Paterson, D (2001)
We characterized the epicardial activation sequence during a norepinephrine (NE)-induced ventricular arrhythmia in anesthetized pigs and studied factors that modulated it. Subepicardial NE infusion caused the QRS complex to invert within a single beat (n = 35 animals, 101 observations), and the earliest epicardial activation consistently shifted to the randomly located infusion site (n = 14). This preceded right atrial activation, whereas the total ventricular epicardial activation time increased from 20 +/- 4 to 50 +/- 9 ms (P < 0.01). These events were accompanied by a ventricular tachycardia and a drop in left ventricular pressure, which were fully reversed after the infusion was stopped. Epicardial pacing at the infusion site mimicked all electrical and hemodynamic changes induced by NE. The arrhythmia was prevented by propranolol and abolished by cardiac sympathetic or vagal nerve stimulation. Focal automaticity was computationally reconstructed using a two-dimensional sheet of 256 x 256 resistively coupled ventricular cells, where calcium handling was abnormally high in the central region. We conclude that adrenergic stimulation to a small region of the ventricle elicits triggered automaticity and that computational reconstruction implicates calcium overload. Interventions that reduce spatial inhomogeneities of intracellular calcium may prevent this type of arrhythmia.